EFFECTIVENESS OF EXPERIMENTAL METHOD ON STUDENTS’ CRITICAL THINKING ABILITIES IN THE MATERIAL OF LIGHT REFRACTION IN GRADE 5 STUDENTS - Nurmaulida, Fiya Alfiyah; Zulaiha, Fanni; Nurbait, Syifa (Jurnal Ilmu Pendidikan Dasar (JIPDA), 2025)
Abstract This study aims to determine the level of effectiveness of the experimental method on students’ critical thinking skills in the refraction of light material in grade 5 students. This study uses a quantitative approach with a quasi-experimental design with a one-group pretest-posttest design. The instruments used are test instruments in the form of descriptions, questionnaires for students and interview guidelines for grade 5 teachers. The results of the study indicate that the experimental method improves students’ critical thinking skills in the refraction of light material in grade 5 students with an average pretest score of 62.14 and a standard deviation of 9.297 and an average posttest score of 81.43 with a standard deviation of 8.536. In addition, the results of the paired t-test (Paired Samples t-test) with a P <.001 result and a t-value of 10.157 indicate that there is a significant influence between the experimental method on students’ critical thinking skills and the results of the N-Gain test with an average of 0.5116 indicate that the level of effectiveness of the experimental method on students’ critical thinking skills is included in the moderate category. Thus, it can be concluded that the experimental method can improve students’ critical thinking skills on the refraction of light material in grade 5 students with an effectiveness level in the moderate category.